Defining ‘Professionalism’ : A Social Constructivist Analysis of Generational Conceptions - Fay, Martha J.; Casetta, Esau; Cleereman, Rebecca; Leis, Alex; Gillespie, Katie (My University, 2018)
Previous research has linked the concept of professionalism in several fields such as marketing, journalism, and healthcare with ethical behavior of employees (Ellingson, 2011). However, none of these studies have provided a clear definition of professionalism. Given the general importance of ethics in organizations, a consistent definition of professionalism seems important to identify (Faber, 2011). Studies have also shown that various generations view what comprises ethical behavior differently (Schullery, 2013). Structuration theory suggests that both professionalism and ethics are socially constructed through interaction; as such, understanding how people believe professionalism is enacted (and thereby defined) seems vitally important, as does examining whether this definition varies between generations. Using thematic analysis of open-ended survey responses from participants in a variety of age ranges and fields, this study examines how different generations conceive of what communicative behaviors constitute professionalism.
Color poster with text, charts, and images.
Keywords: Posters; Professional employees - Perceptions - United States.; Professional ethics